Immunohistochemical detection of serotonin in the kidney and adrenal of porcupine (Hystrixcristata) - Tarakci, B. Gencer; Gur, F. M.; Timurkaan, S.; Girgin, M.; Yalcin, M. H. (Agricultural Research Communication Centre, 2017)
In the present study, the existence of serotonin immunoreactivity was investigated in the adrenal gland and kidney of porcupine, Hystrix cristata, using immunohistochemical techniques as a pioneer attempt. Serotonin immunoreactivity was detected in adrenal medullary cells, distal tubules and collecting duct cells in kidney.
Keywords: Adren; Immunohistochemistry; Kidney; Porcupine; Serotonin